The tourism and peace nexus - Farmaki, Anna (My University, 2017)
Tourism has been heralded as a contributor to peace, however, the inconclusive findings of empirical studies render the need for a consolidation of theory that has in so far relied on case studies and the adoption of the contact hypothesis. Informed by political science theory, this paper proposes a methodological framework that can guide future research and aims to serve as a benchmark for researchers interested in temporal issues pertaining to conflict, peace and tourism. Signalling a departure from the simplistic notion that contact through travel contributes to social integration, the paper adopts a holistic conceptualisation of the multi-faceted and complex system of actors, sectors and dimensions of tourism spanning at the social, economic, political and environmental levels.
Keywords: Conflict; Peace; Political science theory; Reconciliation; Tourism